Data Kependudukan Sebagai Sumber Belajar Pembelajaran Geografi Dengan Metode Outdoor Learning Kelas Xi Ips Ma Al- Hidayah 1 Purwareja Klampok - Wahyuningsih, Diyah; Hardati, Puji; Indrayati, Ariyani (Jurusan Geografi, Fakultas Ilmu Sosial, Universitas Negeri Semarang, 2017)
This research objective is to find out how the students’ activities and the learning results in learning Geography by using population data as a learning resources by applying the method of outdoor learning at MA Al-Hidayah 1 Purwareja Klampok. The variable in this research is the students’ activities and learning results. Data analysis method used is percentage descriptive method for students’ activities variable and test n-Gain for the learning results. The required data in this research are taken using the method of observation and test. The results of this research are students’ activities based on the highest stage of outdoor learning i.e. the activity of preparation with medium criteria with reaching the number of 69,70%. Students’ activities at the stage implementation is around 58,15% and post -implementation is around 62,12%. Based on the type of students’ activities showed that the lowest activity is oral activity with percentage of 46,67% and the highest activity is the observing activity with percentage of72,53%. Students’ learning results derived from pre-test and post-test with analysed using the test n-Gain and obtained a score of 0,3 and it contains at the low n-Gain criteria. Several factors in which influencing the low of students’ activities and learning results such as (1) there is the trace of playing while the implementation activity of outdoor learning (2) lack of confidence in students’ talking activity and (3) facilities and infrastructure are less supportive of learning process takes place. Penelitian ini bertujuan untuk mengetahui bagaimana aktivitas siswa danhasil belajar dalam pembelajaran Geografi yang menggunakan data kependudukansebagai sumber belajar dengan menggunakan metode outdoor learning yang dilaksanakan di MA Al-Hidayah 1 Purwareja Klampok. Variabel dalam penelitian ini adalah aktivitas siswa dan hasil belajar siswa. Metode analisis data yang digunakan adalah metode deskriptif persentase untuk variabel aktivitas siswa dan uji n-Gain untuk hasil belajar. Data yang dibutuhkan dalam penelitian ini diambil menggunakan metode observasi dan tes. Hasil dari penelitian ini adalah aktivitas siswa berdasarkan tahapan outdoor learning yang paling tinggi yaitu aktivitas siswa pada tahap persiapan dengan kriteria sedang dengan angka 69,70 %. Aktivtitas siswa pada tahap pelaksanaan sebesar 58,15 % dan tahap pasca pelaksanaan sebesar 62,12%. Berdasarkan jenis aktivitas siswa hasil penelitan menunjukkan bahwa aktivitas yang paling rendah adalah aktivitas berbicara dengan persentase sebesar 46,67 % dan yang paling tinggi adalah aktivitas mengamati dengan persentase sebesar 72,53 %. Hasil belajar yang diperoleh siswa menunjukkan nilai n-Gain sebesar 0,3 dan termasuk kedalam kriteria n-Gain rendah. Faktor yang mempengaruhi rendahnya aktivitas siswa dan hasil belajar siswa antara lain (1) ada kesan main-main dari siswa pada saat kegiatan pelaksanaan outdoor learning, (2) kurangnya kepercayaan diri siswa dalam kegiatan berbicara dan (3) sarana dan prasarana yang kurang mendukung saat pembelajaran berlangsung.